Serum Uric Acid and Risk of Chronic Heart Failure: A Systematic Review and Meta-Analysis - Miao, Lina; Guo, Ming; Pan, Deng; Chen, Pengfei; Chen, Zhuhong; Gao, Jie; Yu, Yanqiao; Shi, Dazhuo; Du, Jianpeng (Frontiers in Medicine, 2021)
Objectives: A systematic literature review and meta-analysis was performed to investigate the relationship between serum uric acid (SUA) and the risk of chronic heart failure (CHF). Methods: The Embase, PubMed, Web of Science and Cochrane Library databases were searched up to 5 April 2021 for relevant publications. Random effects model was used to pool data. STATA15.0 software was used to perform meta-analysis. Heterogeneity was assessed using the Cochran Q statistic (significance level of P<0.10) and I2 statistics (significance level of 50%). Results: Ultimately, 18 publications reporting adverse events in CHF patients were included. The results indicate reveal associations between a high level of SUA and the risk of all-cause mortality (HR 2.24, 95% CI 1.49-3.37), cardiovascular mortality (HR 1.14, 95% CI 1.06–1.23), and the composite of death or cardiac events (HR 1.26, 95% CI 1.01–1.56) in CHF patients. A 1 mg/dL increase in serum uric acid led to 4% (HR 1.04, 95% CI 1.02–1.05) and 9% (HR 1.09, 95% CI 1.03–1.17) increases in the risk of all-cause mortality and the composite endpoint of death or cardiac events in CHF patients, respectively. Conclusion: Serum uric acid is positively associated with the risk of adverse events in CHF patients. This systematic review and meta-analysis has been registered at PROSPERO as CRD42021247084.